2018
DOI: 10.1039/c8ra05017a
|View full text |Cite
|
Sign up to set email alerts
|

Grafted iron(iii) ions significantly enhance NO2 oxidation rate and selectivity of TiO2 for photocatalytic NOx abatement

Abstract: By grafting small amounts of iron ions onto TiO2, the rate of photocatalytic oxidation of NO2 is increased by a factor of 9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The importance of photocatalysis in fundamental and applied science has expanded tremendously over the last decades (Schneider et al, 2014 ; Augugliaro et al, 2015 ; Balzani et al, 2015 ; Romero and Nicewicz, 2016 ). Next to applications of heterogeneous photocatalysis in the removal of air pollutants (Ballari and Brouwers, 2013 ; Patzsch et al, 2018 ) and waste-water treatment (Alfano et al, 2000 ; Malato et al, 2009 ), a variety of applications in the field of organic synthesis (Friedmann et al, 2016 ; Bloh and Marschall, 2017 ) have emerged, particularly using molecular photoredox catalysts (Zeitler, 2009 ; Romero and Nicewicz, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of photocatalysis in fundamental and applied science has expanded tremendously over the last decades (Schneider et al, 2014 ; Augugliaro et al, 2015 ; Balzani et al, 2015 ; Romero and Nicewicz, 2016 ). Next to applications of heterogeneous photocatalysis in the removal of air pollutants (Ballari and Brouwers, 2013 ; Patzsch et al, 2018 ) and waste-water treatment (Alfano et al, 2000 ; Malato et al, 2009 ), a variety of applications in the field of organic synthesis (Friedmann et al, 2016 ; Bloh and Marschall, 2017 ) have emerged, particularly using molecular photoredox catalysts (Zeitler, 2009 ; Romero and Nicewicz, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study addresses several important aspects of photocatalysis at well-defined anatase TiO2 crystals, and, based on that, provides also a good platform for a more general reconsideration of factors of the reaction rate of oxygen reduction by photogenerated electrons, which is known to play a key role in photocatalytic degradation of organic compounds, 34,35,37,56,67,68,[70][71][72] especially when TiO2 particles are relatively large (size > 1 m). 52 Finally, we found that only platinized {101} facets contribute to photocatalysis.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is still challenging to inhibit recombination the photoinduced electrons and holes on the photocatalysts’ surface. Based on the atomic compositions, arrangement states and bonding networks termination on the surface of semiconductor‐based photocatalysts, some effective atomic‐level surface charge separation strategies, such as surface vacancy formation, [ 150–152 ] surface atom doping, [ 153–155 ] single atom loading [ 156–158 ] and ion grafting, [ 159–161 ] have been proposed to directly regulate the in‐plane and 3D spatial surface electronic configuration. Such strategies allowed more surface charges to effectively migrate to specific catalytic active sites, thereby improving the photocatalytic activity ( Figure ).…”
Section: Atomic‐level Surface Charge Separation Strategiesmentioning
confidence: 99%